DOA SEBAGAI SARANA KOMUNIKASI DENGAN SANG PENCIPTA - Najra Nabiila Hajar (Jurnal Studi Islam, 2022)
This research is discussed to find out the importance of prayer as a means of communication with the Creator. Prayer is intended as worship to Allah SWT. Prayer is the essence of worship. This is like the hadith of the Prophet Muhammad which reads "Prayer is Worship". Therefore, it is proper for us as creatures to multiply prayers. Prayer is the most important theme in the Qur'an as it has been taught by the Prophets and Messengers of Allah, and all kinds of prayers for all matters have been enshrined in the Qur'an. The urgency of prayer in Islamic teachings is to show that a human being is a weak creature as well as evidence of human powerlessness. Through prayer, all forms of requests for Allah are granted if we are able to open a good means of communication with the Creator.